Аdsorption of Co2+ and radioactive 60Со by mesoporous TiO2 - H. V. Vasylyeva; I. F. Mironyuk; I. M. Mykytyn (Хімія, фізика та технологія поверхні)
Introduction shows the important of this scientific direction. 60Co with half-life of 5.3 years is one of the few anthropogenic, gamma-emitting radionuclides, that can be detected in aquatic environments affected by liquid effluent discharged from nuclear facilities. The need for control of the content of 60Co in the environment, determines the search for new adsorption materials with high adsorption capacity and chemical, thermal, and radiation resistance.